An Empirical Five-Pillar Framework For Sustainability In Management Education - Steven Greenland; Muhammad Saleem (Universitas Pakuan, 2025)
Sustainability has become a strategic priority in management education as higher education institutions are increasingly expected to prepare future leaders capable of addressing complex global environmental, social, economic, and governance challenges. Nevertheless, the development of sustainability-oriented curricula often lacks empirically grounded frameworks that reflect students’ perceptions and contemporary sustainability priorities. Addressing this gap, the present study proposes and validates an empirical five-pillar framework for sustainability in management education. Using a sequential mixed-methods approach, the study first explored students’ perceptions of sustainability through qualitative interviews conducted with business and law students at an Australian higher education institution. The qualitative findings informed the development of a structured survey administered to 383 respondents. Exploratory Factor Analysis (EFA) and Partial Least Squares Structural Equation Modeling (PLS-SEM) were employed to identify and validate the underlying dimensions of sustainability. The findings reveal five interrelated pillars of sustainability: social, political, environmental, corporate, and economic sustainability. Among these dimensions, social sustainability emerged as the most influential pillar, followed by political and environmental sustainability. The study further identifies variations in sustainability perceptions across demographic and educational contexts, including gender, age, academic level, and student status. The proposed framework extends conventional three- and four-pillar sustainability models by introducing corporate sustainability as a distinct and empirically validated dimension. The study contributes theoretically by offering a data-driven sustainability framework for management education and contributes practically by providing curriculum developers, business schools, and policymakers with a structured model aligned with the United Nations Sustainable Development Goals (SDGs). The framework may support the design of more responsive and future oriented sustainability education strategies in higher education institutions.